Responses of summer phytoplankton community to drastic environmental changes in the Changjiang (Yangtze River) estuary during the past 50 years - Jiang, Zhibing; Liu, Jingjing; Chen, Jianfang; Chen, Quanzhen; Yan, Xiaojun; Xuan, Jiliang; Zeng, Jiangning (Water research (Oxford), 2014)
The phytoplankton community in the Changjiang Estuary is subject to intensive physical and chemical stresses because of human- and climate-driven changes. We obtained historical data on summer phytoplankton communities from 1959 to 2009 to explore responses to long-term environmental changes. The nitrogen (N) and phosphorus (P) concentrations and ratios (N/P and N/Si) increased because of persistent riverine loading, but silicon (Si) levels remained constant. Climatic changes and extensive water diversions and withdrawals (sediment retention) resulted in a series of physical alterations, including increased temperature, turbidity reduction, and river plume shrinkage. These changes induced a dramatic increase in microalgal biomass (cell density and chlorophyll a) with a decreasing diatom-dinoflagellate ratio, and exacerbated harmful algal blooms. In the past dominant net-collected species were usually chain-forming diatoms; however, more recently, large dinoflagellates and filamentous cyanobacteria dominate. This was not consistent with information from water samples (co-dominated by small dinoflagellates), because of the loss of solitary species collected using a 76-μm net. The dominant species shifted from temperate-subtropical/eurythermal to subtropical-tropical/eurythermal taxa in the warmer water caused by global warming and hydrographic changes. There was also an increased dominance of euryhaline/high-salinity species due to increase in Kuroshio transport and the northward Taiwan Warm Current and reduction in Changjiang Diluted Water. All these changes in phytoplankton communities appear to be closely related to an increase in anthropogenic activities and climatic changes.